Gastronomi Permakultur sebagai Daya Tarik Wisata di Rumah Kayu Permakultur Kabupaten Bandung Barat - Amelia, Bunga Raihan; Turgarini, Dewi; Putri, Dias Pratami (JURNAL GASTRONOMI INDONESIA, 2025)
Sustainable tourism development is important to implement due to the implementation of increasingly uncontrolled development in a country. Rumah Kayu Permaculture is a gastronomic tourism destination in West Bandung Regency that applies permaculture principles. Permaculture is an ecological design that designs food security in a sustainable manner that can be an efficient tourism development solution without damaging the environment. Therefore, this study aims to determine the gastronomic components at Rumah Kayu Permaculture and permaculture gastronomy tour packages. The method applied in this research is a qualitative approach, with data collection through interviews, observations, literature analysis, and documentation studies. The attraction of Rumah Kayu Permaculture has great potential for the development of gastronomic tourism which can be developed through attractive tour packages for tourists. Travel patterns and tour packages were designed and tested by researchers based on the analysis of gastronomic components and opinions from stakeholders.